Trends in outcome and patient composition in dilated cardiomyopathy in Sweden over time. (25th November 2020) - Sjoland, H; Silverdal, J; Bollano, E; Pivodic, A; Fu, M
Abstract: Background: We studied prognosis and patient composition over time in dilated cardiomyopathy (DCM): a well-defined category of heart failure (HF), often affecting younger individuals. We expected improved prognosis over time, due to emerging diagnostic and therapeutic options. Methods: All patients from the Swedish Heart Failure Registry (SwedeHF) fulfilling criteria for DCM (exclusion of ischemic, valvular, or alcoholic etiology and affirmed by clinical judgment in the protocol) (n=3739), were analyzed with respect to three time periods of inclusion in the registry, 2003–2007 (n=814), 2008–2011 (n=1448), 2012–2016 (n=1477), regarding mortality, transplantations, and hospital admissions during one year after inclusion. Results: Over the three time periods, registered cohorts were older with time (mean 59.3 years/ 60 years/ 61.0 years, p=0.0035), and the proportion of females incresased (24.1% / 27.2% / 30.7%, p=0.0006). For clinical variables, the distribution of left ventricular ejection fraction (LVEF) with time showed significantly higher LVEF (p=0.0024), and functional classification (NYHA) showed lower class (p=0.0011). Hypertension as a comorbidity (i.e. not judged to be responsible for HF) was more frequently occurring with time: (34.0%/ 40.6%/ 44.1%, p<0.0001). As for HF treatment: use of device increased (p<0.0001 for categorical combinations), mineralocorticoid receptor antagonists (MRA) increased (41.9%/ 37.3%/ 46.7%, p=0.0023), and diuretics dropped (76.1%/ 71.1%/ 67.0%, p≤0.0001) in the different cohorts with time. Mortality (6.9%, 5.1%, 5.5%), transplantation (0.5%, 0.8%, 0.6%) and hospital admissions for HF (28.4%, 26.3%, 24.6%) were stable over time (ns for all), whereas cardiovascular (CV) (33.8%, 33.8%, 29.7%, p=0.043) and all cause admissions (39.1%, 38.8%, 33.7%, p=0.0099) decreased. After adjustment for age, sex, LVEF, NYHA, hypertension and device treatment only all cause admissions remained significantly decreased. Conclusion: In this nationwide study between 2003–2016, one-year outcome in DCM in Sweden remained stationary over time, despite advances in HF therapy. During the time period, we observed a continuous change in the clinical profile in the DCM population. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Region Västra Götaland agreement concerning research and education of physicians.